Perancangan Focus Group Discussion Sebagai Ruang Partisipasi Masyarakat Dalam Membangun Desa Berbasis Website - Wijaya, Masesa Angga; Perdana, Chepy (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2023)
Participation in the form of joint discussions between the village government and the village community is needed in developing the village. However, currently the village government is holding discussions on village development, only a portion of the community is aware of the discussion, so that only a portion of the community is present. In addition, the results of these discussions did not reach the entire community, so that only part of the community participated in village development. Therefore, a space is needed to accommodate opinions, aspirations or opinions as well as the results of discussions that can be known by the whole community, especially utilizing technological advances. So the solution to overcome this problem is to create a room in the form of a discussion group using a website-based Focus Group Discussion (FGD). It is hoped that this FGD will increase community participation in developing the village. This design research uses a software development method, namely using a waterfall. So with this research it is hoped that the village government and the community can access the discussion room anytime anywhere so that community participation can be comprehensive for the development of the village.